Diagnostic peritoneal fluid aspiration: a simple maneuver to diagnose a major question: a prospective study surgical point of view - Hosni Mohamed, Abdel Hafeez; Abd Almageed, Magdy Khalil; Helmi, Mena Zari; Abdelal, Mohamed El-Sayed (International Surgery Journal, 2017)
Background: A variety of fluids can accumulate in the peritoneal and pelvic cavities including ascites, blood, pus, bile, urine, lymph, cerebral spinal fluid, and mucin. The appearance of some of these fluids by imaging may suggest a specific etiology, but a diagnostic aspiration must be performed in the majority of cases. This review aims to assess critically the value of peritoneal fluid analysis in the diagnosis. Methods: There was prospectively evaluated 80 patients presented with intraperitoneal fluid collection at Sohag University Hospital from July 2016 till July 2017. Physical, chemical, bacteriological and cytological properties of the aspirated peritoneal fluid was studied. Results: The study included 80 patients with intra-peritoneal collection of surgical importance (due to trauma, inflammation, malignancy). Diagnostic aspiration from intra-abdominal collection was routinely done in all cases giving the following results: 20 cases (25%) showed blood in the aspirate, 18 cases (22.5%) showed pus, 11 cases (13.75%) showed bile stained fluid, 9 cases (11.25%) showed gastric contents, 8 cases (10%) showed serosangenous aspirate, 7 cases (8.75%) showed clear fluid aspirate, 4 cases (5%) showed turbid fluid and 3 cases (3.75%) showed small intestinal contents. Conclusions: Diagnostic aspiration from intraperitoneal fluid collection is considered a simple available test that helps in diagnosis of major problematic cases.